Regional Integration in the Face of Modern Challenges: The Case of the EU and ASEAN (International relations and international law Journal, 2023)
The article examines the effectiveness of interaction between states within the framework of regional integration associations in order to collectively overcome the crisis phenomena in the economic, political and social sphere. In the course of the study the tasks of studying the concept of integration as an important category of the modern political system and international relations were defined and solved. The study identifies a number of factors that have become prerequisites for the territorial association of states, such as: issues requiring joint decision-making, territorial proximity, the desire to create an area for export, thereby increasing the competitiveness and productive capacity of large enterprises, as well as meeting the needs of the domestic market. Among the above factors, the collective solution to crisis situations that affect the entire region is one of the important reasons for the association of countries in integration organizations, as integrated associations have more opportunities for rapid and effective decision-making and ensure the practical implementation of strategies in the face of global challenges. This paper analyzes the crisis management policies of the EU and ASEAN countries during the coronavirus pandemic. The outbreak of coronavirus infection has caused a decline in the economy, affected the social sphere, and made adjustments in the policies of individual states and the world community. COVID-19 showed the failure of many social institutions, revealed existing problems, and tested the strength of all spheres of human activity. The result of the work should be considered the identified characteristics of how the integrated actors of international relations responded and what measures were taken to solve the crisis situations in the context of COVID-19, as well as the consequences of the anti-crisis policies implemented. An important point is the assessment of the degree of interaction within the integrated associations themselves, the involvement of each member in the process. In addition, the coherence or, on the contrary, disunity makes it possible to talk about the depth, intensity of integration or its superficial, formal nature in this or that organization.    Key words: regional integration, crisis, COVID-19, EU, ASEAN, challenges of our time.